DNA damage and repair in patients with early chronic kidney disease with or without type 2 diabetes - Andrade-Sierra, Jorge; Pazarín-Villaseñor, Leonardo; García-Sánchez, Andrés; Cardona-Muñoz, Ernesto Germán; Campos-Pérez, Wendy; Martínez-López, Erika; Campos-Bayardo, Tannia Isabel; Román-Rojas, Daniel; Gómez-Hermosillo, Luis Francisco; Casillas-Moreno, Jorge; Echavarría, Raquel; Díaz-de la Cruz, Elodia Nataly; et al. (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionChronic kidney disease (CKD) may improve with appropriate management and close monitoring to prevent the risk of progression to end-stage kidney disease (ESKD). The present study aimed to determine oxidative damage and DNA repair in early kidney disease in patients with and without type 2 diabetes (T2D).MethodsUsing ELISA, serum levels of the oxidative DNA damage marker (8OHdG) and the DNA repair marker (hOGG1) were determined in 100 patients with T2D and 88 without T2D in stages 1, 2, and 3 of CKD.ResultsThe mean number of years of T2D in patients in stages 1, 2, and 3 was 13.93 ± 2.09 years. Significantly increased levels of the 8-OHdG marker were found in stage 3 CKD patients with T2D, 4.96(4.17-5.08) ng/mL vs. 4.13(3.49-4.60) ng/mL without T2D (p=0.006). hOGG1 enzyme levels were significantly decreased in patients with T2D from stage 2, 0.08(0.063-0.082) ng/mL vs. 0.37(0.18-0.36) ng/mL, (p=0.006) and in stage 3 with T2D 0.09(0.08-0.11) ng/mL vs. 0.53(0.07-0.96) ng/mL without T2D (p=0.007). A positive correlation was found between CKD stage and hOGG1 levels in patients with T2D (rho=0.473, p<0.001). 8-OHdG concentration showed an inverse correlation with CKD stage in patients without T2D (rho=-0-274, p=0.030). In conclusion, we found an imbalance of DNA repair enzymes in stages 2 and 3 of CKD in T2D patients and an increase of oxidative DNA damage markers in stage 3 of CKD in T2D patients. Determination of DNA damage and repair markers in the early stages of CKD may facilitate timely diagnosis and treatment of CKD.